Предмет: Алгебра,
автор: nasta270203
Упростите выражение
1) (9a-2)(9а+2)-18a
2)25m^{2}-(5m-7)(5m+7)
3)(b+7)(b-4)+(2-6)(2b+6)
4)4x(3x-10y)-(4x+y)(4x-y)
Ответы
Автор ответа:
0
1) (9a-2)(9а+2)-18a=81a²-4-18a
2)25m^{2}-(5m-7)(5m+7)=25m²-25m²+49=49
3)(b+7)(b-4)+(2-6)(2b+6)=b²-4b+7b-28-4b²+36=-3b²+3b+8
4)4x(3x-10y)-(4x+y)(4x-y) =12x²-40xy-16x²+y²=-4x²-40xy+y²
2)25m^{2}-(5m-7)(5m+7)=25m²-25m²+49=49
3)(b+7)(b-4)+(2-6)(2b+6)=b²-4b+7b-28-4b²+36=-3b²+3b+8
4)4x(3x-10y)-(4x+y)(4x-y) =12x²-40xy-16x²+y²=-4x²-40xy+y²
Похожие вопросы
Предмет: Химия,
автор: belka583belova
Предмет: Математика,
автор: alina723428
Предмет: Қазақ тiлi,
автор: v277701
Предмет: Математика,
автор: Аноним